Highly efficient nondoped blue organic light-emitting diodes based on a star-group tetraphenylethylene-substituted aggregation-induced-emission-active organic fluorescent small molecules. (April 2020) - Xu, Lei; Yu, Yuan; Shi, Jinjin; Cui, Wei; Lv, Xianhao; Cang, Miao; Sun, Qikun; Xue, Shanfeng; Yang, Wenjun
Abstract: Tetraphenylethene (TPE) is a star group exhibiting an excellent aggregation-induced emission (AIE) effect. Although significant progress has been made in the field of organic electroluminescence (EL) based on TPE-substituted emitters, highly efficient and high-color-purity TPE-substituted blue fluorophores with the AIE effect are still very rare. In this paper, a simple and effective molecule— N -phenyl- N -(4-(1-phenyl-1 H -phenanthro[9, 10-d]imidazol-2-yl)phenyl)-4′-(1, 2, 2-triphenylvinyl)-[1, 1′-biphenyl]-4-amine (TPETPAPI)—was designed and synthesized using triphenylamine (donor), phenanthroimidazole (acceptor), and tetraphenylethylene (AIE generator). In tetrahydrofuran solution, the molecule emits little light and the quantum efficiency is low (1.3%); however, the fluorescence is enhanced in the film (73%), exhibiting remarkable AIE properties, thus enabling TPETPAPI to be used in future applications in organic light-emitting diodes. The nondoped device exhibits a low turn-on voltage of 3.0 V, a maximum luminance of 10780 cd m −2, maximum current efficiency of 12.20 cd A −1, and maximum power efficiency of 11.95 lm W −1, with an EL peak at 476 nm. TPETPAPI exhibits the most impressive EL performance reported to date for a TPE-substituted blue fluorophore with AIE' characteristics. Graphical abstract: A new AIE-active blue fluorescent emitter (TPETPAPI) with simple structure is designed and facilely synthesized by a star group TPE-substituted. The non-doped device emitted 476 nm bright blue emission with a maximum luminance of 10780 cd m −2, a maximal current efficiency of 11.95 cd A −1, maximum EQE of 6.05%. The results representing the most efficient (ELmax ≤ 480 nm) blue OLED based on the TPE-substituted AIE-active fluorescent molecule reported thus far. Image 1 Highlights: A new AIE-active blue fluorescent emitter (TPETPAPI) is designed and synthesized. The TPETPAPI exhibits aggregation-induced emission (AIE) properties. The non-doped OLED exhibits excellent device performance with an EQE of 6.05%.